Seeking Baraka: Transformation of Ngaji from Virtual to Conventional among Gen-Xers - Mutaqin, Zezen Zaenal; Mulyawati, Husni; Tsurayya, Rachma Vina; Inayatussahara, Nur Azka (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
This study aims to reveal the transformation of ngaji practices among Generation X audiences, specifically followers of Gus Baha, from virtual to conventional formats. The rapid development of the internet and social media has significantly influenced religious practices, including the proliferation of virtual ngaji. However, despite the convenience of digital platforms, conventional ngaji remains prevalent. This research employs fieldwork and qualitative methods, including in-depth interviews and observations, to investigate why individuals prefer attending traditional ngaji sessions despite the availability of virtual alternatives. The study finds that the cultural concepts of baraka (blessing) and sanad (chain of transmission) are crucial motivators for followers to seek in-person ngaji. Additionally, the research identifies the dual impact of unintended online ngaji—while it extends the reach of Gus Baha’s teachings and bolsters his religious authority, it also poses risks due to the potential for misinterpretation and unauthorized dissemination of content. This study contributes to understanding the dynamics between digital and conventional religious practices and highlights the enduring significance of direct spiritual engagement in contemporary Muslim communities.